Methods for sedimentation study of magnetorheological fluids. (2020) - Prajapati, Hiren; Shahanand, Jas; Nimkar, Hitarth; Lakdawala, Absar
Abstract: Magnetorheological fluids (MR Fluid) have magnetic particles suspended in them and as a result of which they show a tendency to change their behavior in the presence of an applied magnetic field. Inverse thixotropy or sometimes called Rheopexy is property of fluid in which the fluid's viscosity increases with time as it is sheared at a constant rate. MR Fluid, like any other smart fluids, has a large particle size and as a result, it has a tendency in which the suspended particles tend to settle due to the gravitational pull and form hard cake due to agglomeration. This leads to the case in which the fluid loses its property of changing the viscosity with change in magnetic field because there are no particles left suspended in the fluid that can be aligned under the influence of magnetic field. To measure the sedimentation or settling rate of MR fluid, it is necessary to measure particle concentration at various time intervals and at different height of the fluid. In this article, various methods are illustrated with their advantages and limitations, which can provide help in generating the fluid concentration profile.